Ketahanan Keluarga dalam Serial Drama “My Unfamiliar Family” - ., Fatimah; Dian, Agnes; Yunita, Vera (Jurnal Kajian Stratejik Ketahanan Nasional, 2023)
This research uses the drama series entitled "My Unfamiliar Family" from South Korea as the research object. This drama series tells the story of the pressures and challenges, both internal and external, that come to a family and how to adapt. Therefore, an introduction to the challenges and ways to adapt was carried out based on the Characteristics of Resilient Family Protection and Recovery Factors and the Family Resilience Framework. The research method used is a qualitative method with Tzevetan Todorov's narrative analysis model. The results of this research show that the family in the My Unfamiliar Family series can survive and return to a balance point by adapting as mentioned in the theory of family resilience. Specifically, resilience factors related to the adaptation process in this drama series include family communication, open sharing of emotions, agreement between family members, connectedness, belief systems, brotherhood, and collaborative problem solving. Apart from that, this research also has the novelty of using drama series as research objects in the study of family resilience and national resilience.